(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
Polycrystalline samples of Cd substituted cobalt ferrites with composition Co1-xCdxFe2O4 (x = 0.0- 0.6 in steps of 0.1) were prepared by double sintering ceramic method. The samples were sintered at 1050°C for 3 hours. X-ray diffraction pattern of the samples showed single phase cubic spinel structure. It was found that the lattice parameter increases linearly with increasing Cd content following Vegard’s law. The apparent density and X-ray density exhibited similar behavior. The Curie temperature Tc has been determined from the temperature dependence of permeability. It was found that the Curie temperature continuously decreased with increasing Cd content and is attributed to the weakening of JAB exchange interaction. The initial permeability, μ’ increases with increasing Cd content up to x = 0.6 and then decreases. Key words: Co-Cd ferrite; Lattice parameter; Permeability DOI: http://dx.doi.org/10.3329/jbas.v35i2.9429 JBAS 2011; 35(2): 229-235